Transient Early Fine Motor Abnormalities in Infants Born to COVID-19 Mothers Are Associated With Placental Hypoxia and Ischemia - Huan-Yu Liu; Huan-Yu Liu; Juanjuan Guo; Juanjuan Guo; Chang Zeng; Yuming Cao; Yuming Cao; Ruoxi Ran; Ruoxi Ran; Tiancheng Wu; Tiancheng Wu; Guifang Yang; et al. (Frontiers Media S.A., 2022)
Background: Long-term effects of Coronavirus Disease 2019 (COVID-19) on infants born to infected mothers are not clear. Fine motor skills are crucial for the development of infant emotional regulation, learning ability and social skills.Methods: Clinical information of 100 infants born to 98 mothers (COVID-19 n = 31, non-COVID-19 n = 67) were collected. Infants were follow-up up to 9 months post-partum. The placental tissues were examined for SARS-CoV-2 infection, pathological changes, cytokines, and mtDNA content.Results: Decreased placental oxygen and nutrient transport capacity were found in infected pregnant women. Increased IL-2, IL-6, TNF-α, and IFN-γ were detected in trophoblast cells and maternal blood of COVID-19 placentas. Elevated early fine motor abnormal-ities and increased serum TNI (troponin I) levels at delivery were observed in infants born to mothers with COVID-19. Increased abnormal mitochondria and elevated mtDNA content were found in the placentas from infected mothers. The placental mtDNA content of three infants with abnormal DDST were increased by 4, 7, and 10%, respectively, compared to the mean of the COVID-19 group. The Maternal Vascular Malperfusion (MVM), elevated cytokines and increased placental mtDNA content in mothers with COVID-19 might be associated with transient early fine motor abnormalities in infants. These abnormalities are only temporary, and they could be corrected by daily training.Conclusions: Babies born to COVID-19 mothers with mild symptoms appeared to have little or no excess long-term risks of abnormal physical and neurobehavioral development as compared with the infants delivered by non-COVID-19 mothers.